Methodological and instrumental tools of generation of strategies of knowledge-intensive high-tech industries - Романенков, Юрий Александрович; Вартанян, Василий Михайлович; Прончаков, Юрий Леонидович; Зейниев, Теймур Гидаятович (Technology audit and production reserves, 2015)
An approach to the problem of decomposition of decision support for strategic management of the development of knowledge-intensive high-tech industries is proposed in the article. The subject of the research is methodological tools and generates strategies for the development of knowledge-intensive high-tech industries. Complexity and specificity of the strategy development are analyzed. A scheme for generating strategies for the development of knowledge-intensive high-tech industries is considered, as well as the matrix model of the relative effectiveness level assessment of a hierarchical system of business processes in the organization is considered. It is used the original tool of normalized charts as graphic-analytical tools for analysis of the relative effectiveness of substrategies of organization. It is developed optimization mechanism for selecting strategies to improve the competitiveness of the organization, ensuring optimal allocation of resources between the volumes of measures to improve the efficiency of certain business processes in the organization. Algorithmic and software tools for modeling business processes in functionality are systematized.